Andean Archaeology III
XI, 523 p.
Keywords: This book is intended to continue the dynamic, current problem-oriented approach to the field of Andean Archaeology that started with Andean Archaeology I and Andean Archaeology II. In this volume, the strong cultural differences between northern and southern regions of the Central Andes are examined and the conditions under which these differences evolved are explored. Andean Archaeology III combines up-to-date research, diverse theoretical platforms, and far-reaching interpretations.